Características do processo sucessório dos programas de pós-graduação stricto sensu em contabilidade no Brasil - Pablo Henrique de Oliveira Queiroz (2023)
The present study had the general objective of identifying the direct or indirect strategies used by Brazilian graduate programs in the accounting area to prepare their coordinators for the succession process. Therefore, this exploratory study, with a qualitative approach, employed survey techniques as a research strategy, using a questionnaire and semi-structured interviews as data collection instruments. The sample of this study was represented by the 19 valid answers obtained in the application of the questionnaire and the 6 interviews carried out. The analysis of the questionnaire took place through the use of descriptive analysis techniques, while the interviews were submitted to the template analysis technique, carried out based on the Relay Race Theory proposed by Dyck et al. (2002). The main results found show that the stricto sensu graduate programs in accounting have some level of practices related to the succession process, according to the relevant literature. It was found that in 50% of the participating programs the prior identification of the successor, in 100% the existence of a talent bank, in 67% the preparation of coordinators, in 100% the existence of an emergency plan, no strategy aimed at helping dismissals, in 83% the cooperation of the current coordinator and members of the faculty, and in 67% practices related to communication of what happened and the successor. However, even on occasions when it was possible to identify direct or indirect succession strategies in the interviewees' reports, it is perceived that there is precariousness in their use and that discussions regarding the succession of postgraduate program coordinators are still incipient, with strategies formed mainly from informal practices or the program's internal regulations. The reports still show a lack of interest in assuming the role on the part of the teachers and focus on the existing burdens in the exercise of the function, which are recognized as possible limitations for the implementation of a succession plan, since, if there is no interest, it is not possible carry out prior identification of the successor, enable his/her training, as well as smooth the management transition with the cooperation of those involved and effective communication.